Peritoneal Tuberculosis in an Immunocompetent, Unknown Risk Patient - Yutaka Tomizawa; Emmanuelle B. Yecies; Fiona E. Craig; Adam Sohnen (Case Reports in Gastrointestinal Medicine)
A 36-year-old man with no significant past medical history presented with two-month abdominal distention, night sweats, and weight loss of 15 Ib. He had no known exposure to tuberculosis. PPD test was negative prior to the hospital admission. Physical examination was notable for new onset ascites, but no superficial lymphadenopathy or stigmata of chronic liver disease was found. CT scan demonstrated enlarged mesenteric lymph nodes, and prominent retroperitoneal lymph nodes along with moderate ascites and omental infiltration. Diagnostic paracentesis yielded WBC of 295/mm3, lymphocytic predominance (70%), and serum ascitic albumin gradient of 0.1, consistent with exudate. Both the ascitic culture and AFB smear were negative, and ascitic cytology revealed nonmalignant cells. Exploratory laparoscopy for excisional biopsy of mesenteric lymph nodes was performed. Pathologic findings revealed caseous granulomas with scattered multinucleated giant cells. Mesenteric lymph node tissue culture subsequently grew Mycobacterium tuberculosis complex and the diagnosis of peritoneal tuberculosis was confirmed. The patient was started on quadruple therapy. A couple of days after the antibiotics were started, the small bowel obstruction started to resolve with resumption of bowel movements and tolerance of oral intake. A week later, ascites stopped accumulating and fever was no longer noted. He has been well and continues to be under observation.